2015
DOI: 10.5951/jresematheduc.46.3.0331
|View full text |Cite
|
Sign up to set email alerts
|

A Kindergarten Number-Sense Intervention With Contrasting Practice Conditions for Low-Achieving Children

Abstract: The efficacy of a research-based number-sense intervention for low-achieving kinder-gartners was examined. Children (N = 126) were randomly assigned to 1 of 3 conditions: a number-sense intervention followed by a number-fact practice session, an identical number-sense intervention followed by a number-list practice session, or a business-as-usual control group. The interventions were delivered in a small-group setting over 24 half-hour lessons. Both intervention groups performed better than controls on measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 52 publications
(78 reference statements)
1
35
0
3
Order By: Relevance
“…In light of the importance of early mathematical skills, there is an extensive interest in conducting early intervention in mathematics (e.g., Dyson et al, 2011;Dyson, Jordan, Beliakoff, & Hassinger-Das, 2015;Griffin, 2007;Mononem & Aunio, 2016;Nunes et al, 2007;Nunes et al, 2015;Shanley et al, 2017;Toll & Van Luit, 2012), of which several have been determined to be efficient. A review of intervention studies by Gersten et al (2005) as well as the meta-analysis of Gersten et al (2009) suggest that the most effective instructional design for struggling learners is one that is both systematic and explicit.…”
Section: Early Numeracy Interventionsmentioning
confidence: 99%
“…In light of the importance of early mathematical skills, there is an extensive interest in conducting early intervention in mathematics (e.g., Dyson et al, 2011;Dyson, Jordan, Beliakoff, & Hassinger-Das, 2015;Griffin, 2007;Mononem & Aunio, 2016;Nunes et al, 2007;Nunes et al, 2015;Shanley et al, 2017;Toll & Van Luit, 2012), of which several have been determined to be efficient. A review of intervention studies by Gersten et al (2005) as well as the meta-analysis of Gersten et al (2009) suggest that the most effective instructional design for struggling learners is one that is both systematic and explicit.…”
Section: Early Numeracy Interventionsmentioning
confidence: 99%
“…Nonetheless, non-CAI can produce similar, if not stronger effects in samples of children similar to those in the present study. Dyson, Jordan, Beliakoff, and Hassinger-Das (2015) demonstrated that a supplemental Kindergarten number sense intervention delivered to small groups of students had substantially positive impacts on children's number sense, arithmetic fluency, and mathematics calculation achievement (effect sizes = 0.32 to 0.82). In contrast, Clarke et al (2015) reported negligible effects (p-values = .0517 to .89) of a core Kindergarten mathematics curriculum on four mathematics outcomes (effect sizes = -0.008 to .108).…”
Section: Discussionmentioning
confidence: 99%
“…Lago and DiPerna (2010) put forth that a variety of tests have been developed to measure number sense, yet emphasize that a very few of the assessment tools examine reliability and validity. Number Sense Screener (NSS) is one of the assessment tools used in many different studies in order to measure number sense of preschool children and its validity and reliability are proven in line with longitudinal studies (Jordan et al, 2006;Lago & DiPerna;2010;Jordan et al, 2012a;Dyson, Jordan, Beliakoff, Hassinger-Das, 2015;Starr, DeWind & Brannon, 2017). Number Sense Screener is an important assessment tool for being a psychoeducational assessment instrument to monitor number development, predict later mathematics achievement, and identifies children at risk and to prepare effective intervention programs accordingly (Jordan et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%